2020
DOI: 10.5194/acp-20-7829-2020
|View full text |Cite
|
Sign up to set email alerts
|

On the climate sensitivity and historical warming evolution in recent coupled model ensembles

Abstract: Abstract. The Earth's equilibrium climate sensitivity (ECS) to a doubling of atmospheric CO2, along with the transient climate response (TCR) and greenhouse gas emissions pathways, determines the amount of future warming. Coupled climate models have in the past been important tools to estimate and understand ECS. ECS estimated from Coupled Model Intercomparison Project Phase 5 (CMIP5) models lies between 2.0 and 4.7 K (mean of 3.2 K), whereas in the latest CMIP6 the spread has increased to 1.8–5.5 K (m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
129
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 28 publications
21
129
0
Order By: Relevance
“…Effective radiative forcing (ERF) has gained acceptance as the most useful measure of defining the impact on Earth's energy imbalance to a radiative perturbation (Myhre et al, 2013;Boucher et al, 2013;Forster et al, 2016). These perturbations can be anthropogenic or natural in origin and include changes in greenhouse gas concentrations, aerosol burdens, land use characteristics, solar activity and volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective radiative forcing (ERF) has gained acceptance as the most useful measure of defining the impact on Earth's energy imbalance to a radiative perturbation (Myhre et al, 2013;Boucher et al, 2013;Forster et al, 2016). These perturbations can be anthropogenic or natural in origin and include changes in greenhouse gas concentrations, aerosol burdens, land use characteristics, solar activity and volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Richardson et al (2019) showed that using ERF rather than radiative forcing (RF) reduces the need for forcing-specific efficacy values (the temperature response per unit forcing), first introduced by Hansen et al (2005) as an observation that different values of λ better predicted T for different forcing agents under RF. Conversely, evaluating ERF is less straightforward than RF, requiring climate model integrations, and numerous different methods of calculating ERF exist with their own benefits and drawbacks (Shine et al, 2003;Gregory et al, 2004;Hansen et al, 2005;Forster et al, 2016;Tang et al, 2019;Richardson et al, 2019). The difference between ERF and RF is that ERF includes all tropospheric and land surface adjustments, whereas RF only includes the adjustment due to stratospheric temperature change (Sherwood et al, 2015;Myhre et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case the temperature is nevertheless colder than observed in the 1960s to early 2000s, which is a consequence of the temporal evolution of the aerosol forcing that increased up until the 1970s and then changed only little afterwards as greenhouse gas forcing rose more steadily in time (Figure ). It is therefore difficult to compensate a high climate sensitivity only with strong aerosol cooling and obtain a realistic temporal evolution (Zhao et al, ), and the behavior seen in the two‐layer model simulation here can be seen in several of the recent CMIP6 models with high ECS (Andrews et al, ; Flynn & Mauritsen, ; Golaz et al, ; Held et al, ). The planetary imbalance in year 2011 in both cases, 0.76 W m −2 for the standard setup, and 0.80 W m −2 with high climate sensitivity and strong aerosol cooling, are close to but slightly higher than the observed estimate of 0.71 W m −2 ± 0.10 for the period 2005–2015 (Johnson et al, ).…”
Section: Modeled Centennial Warmingmentioning
confidence: 99%
“…However, it is also possible that such sensitive models have been discarded, and the anecdotal evidence given here supports this, but it is not possible to assert how widespread this practice is. In this regard it is interesting that some CMIP6 models do exhibit larger climate sensitivities than seen in CMIP3 and CMIP5; however, there is evidence that this reflects a community‐wide systematic shift in the representation of extratropical clouds, and not simply random fluctuations (Flynn & Mauritsen, ; Zelinka et al, ).…”
Section: Closing Remarksmentioning
confidence: 99%